Traumatic Globe Luxation: When to Save It? - Awina Rayungsista; Susy Fatmariyanti (Department of Ophthalmology, Faculty of Medicine, Universitas Airlangga, 2022)
Introduction: Globe luxation is a rare case and is one of the trauma conditions contributing to the number of blindness worldwide. Its etiology is divided into three categories: spontaneous, voluntary, and post-traumatic. Case presentation: A 21-year-old man was referred with a chief complaint of left eye protruding and painful blind eye after a car accident 12 hours before being consulted. Systemic condition revealed anemia with bilateral pneumonia and was confirmed as COVID-19, an asymptomatic condition. Visual acuity of both eyes was > 2/60 lying position with no light perception, respectively. During surgery, we found necrotic ocular surface and choroidal prolapse. Enucleation was chosen because of poor eyeball conditions and no visual potential. Conclusion: In multiple trauma cases, either eye or systemic conditions must be considered. Although saving the eyeball is the primary treatment choice, enucleation should be considered if the eyeball’s condition is poor and has no visual potential.